PENGARUH VARIASI TEKANAN PEMBRIKETAN, PEREKAT, dan TEMPERATUR AWAL TUNGKU TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET ARANG SAMPAH KOTA (MSW) TERSELEKSI (The Effect of Briquetting Pressure, Binder, and Initial Furnace Temperature Variations on Characteristics of Municipal Solid Waste (MSW) Combustion) - , Novi Caroko, Prof. Dr. Ing. Ir. Harwin Saptoadi, M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The population growth in Indonesia would also increase the national energy consumption per year. National energy consumption is expected to increase from 674 million Barrels of Oil Equivalent (BOE) in 2002 to 1680 million BOE in 2020,that would be approximately increase 2.5 times or increase by an average growth rate of 5.2 % per year. On the other hand, due to an increase in population will also increase the volume of waste that generated. It can be solved by processing waste into a form that is more valuable, by making waste as part of the alternative renewable energy sources (renewable energy). This study uses selected Municipal Solid Waste (MSW) in the form of bamboo, banana leaves, styrofoam, and plastic as raw materials for briquettes. Waste with compositions of 75 % organic (consists of 50 % banana leaves and 50 % bamboo) and 25% an organic (consists of 50 % styrofoam and 50 % plastic) were destroyed in advance so that it passes 20 mesh size, then pyrolysis process was carried out to obtain charcoal. Briquetting use percentage of binder by 20 % of the total weight 3 g briquette, variation types of binder are starch, tar, and the combination of tar and starch, and with a variation of the briquetting pressures of 200 kg/cm 2 , 250 kg/cm 2 and 300 kg/cm 2 . Characteristics examinations of the combustion use a constant heat flux method varied in the initial oven temperature 300 o C, 400 o C, and 500 o C. Characteristics occurred in combustions are Ea, ITVM (Initiation Temperature of Volatile Matter), ITFC (Initiation Temperature of Fixed Carbon), PT (Peak of weight loss Temperature) dan BT (Burning out Temperature). From investigation it is known that the higher pressure will result in lower burning rate, lower heat release, lower ITVM, lower ITFC, lower PT, lower BT, and lower the activation energy. Briquettes with Tar bindings has the highest burning rate, highest heat release, lowest ITVM, lowest ITFC, highest PT, highest BT, and lowest activation energy compared with a Tar + starch binding briquettes and also starch binding briquettes. The higher initial furnace temperature will result in higher burning rate, higher heat release, higher ITVM, higher ITFC, the higher PT, higher BT and higher activation energy.